Evaluasi dan Redesain Instalasi Pengolahan Air Limbah (Studi Kasus: Hotel X Kota Jambi) - Monik Kasman; Marhadi Marhadi; Imam Mahdi Azwar (Jurnal Daur Lingkungan, 2022)
Hotels produce wastewater as much as 80% of the total use of clean water, the wastewater is categorized as domestic wastewater. Hotel X is a 4-star hotel with a need for clean water of 64,396 m3/day and the waste water produced is 49.33 m3/day. Based on observations and evaluations, it was concluded that Hotel X's wastewater was treated at the WWTP with performance that was still not optimal. So that the method used in this research is descriptively analyzing primary and secondary data, then proceed with evaluation and redesign of certain WWTP units based on existing conditions in the field. Laboratory test results show that the parameters that do not meet the quality standards are TSS 136 mg/L, BOD5 56 mg/L, and COD 174 mg/L, so the units that need to be evaluated based on existing conditions consists of grit chamber units, equalizing tanks, anaerobic tank, aerobic tanks, sludge tanks and sedimentation tanks. Based on the results of the evaluation on the existing WWTP unit at Hotel X, there are WWTP units that need to be optimized, namely equalizing tanks and aerobic tanks, where the detention time exceeds the design criteria. Redesign of dimensional changes to the equalizing tank and aerobic tank units. Based on the calculation results, the detention time in the equalizing tank was 8.5 hours and in the aerobic tank 14.38 hours. The equalizing tank unit has been modified to a depth of 2 m to reduce detention time in the initial processing to 6.8 hours, while for the aerobic tank 2 unit, it is modified to a width of 2.5 m and a length of 2.5 m, the length and width of the aerobic tank unit 2 is equated with the size of tube 1 to reduce detention time in processing to 7.6 hours.